Secure distributed ledgers to support IoT technologies data - Concepción-León, A.; Endler, M. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2019)
Blockchain and Tangle are data structures used to create an immutable public record of data insured by a network of peer-to-peer participants that maintains a set of constantly growing data records known as ledgers. Blockchain and Tangle technologies are a decentralized solution that guarantees the exchange of large amounts of trusted messages, among billions of connected IoT devices, which are very valuable as long as they are valid and complete. This highly encrypted and secure peer-to-peer messaging mechanism is adopted in this project to manage the processing of IoT transactions and the coordination between the devices that interact with the process. To maintain transactions private, secure and trustless, the distributed consensus algorithms are responsible for validating and choosing transactions and recording them in the global ledger. The results showed that the speed of the consensus algorithms can affect the creation in real time of reliable stories that track the events of the IoT networks. After incorporating Complex Event Processing that allows selecting only those high level events, it is possible to obtain an improvement in many situations. The result is a Middleware system that provides a framework for the construction of large-scale computer applications that use Complex Events Processing and different decentralized ledgers such as the blockchain of Ethereum or IOTA Tangle, for secure data storage.